2000
DOI: 10.1143/jpsj.69.2145
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent State of Charge Density Wave and Spin Density Wave in One-Dimensional Quarter Filled Band Systems under Magnetic Fields

Abstract: We theoretically study how the coexistent state of the charge density wave and the spin density wave in the one-dimensional quarter filled band is enhanced by magnetic fields. We found that when the correlation between electrons is strong the spin density wave state is suppressed under high magnetic fields, whereas the charge density wave state still remains. This will be observed in experiments such as the X-ray measurement.KEYWORDS: one-dimensional quarter filled band, charge density wave, spin density wave,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It is found by Kobayashi et al [7,8] and Mazumdar et al [9] that the coexistent state of 2k F -SDW and 2k F -CDW is stabilized when the next nearest neighbor Coulomb interaction (V 2 ) and the dimerization of the energy band are considered. On the other hand, even if the dimerization is absent, it is indicated that the 2k F -SDW and 2k F -CDW coexists by Tomio and Suzumura [11,12] and the present author [13,14].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…It is found by Kobayashi et al [7,8] and Mazumdar et al [9] that the coexistent state of 2k F -SDW and 2k F -CDW is stabilized when the next nearest neighbor Coulomb interaction (V 2 ) and the dimerization of the energy band are considered. On the other hand, even if the dimerization is absent, it is indicated that the 2k F -SDW and 2k F -CDW coexists by Tomio and Suzumura [11,12] and the present author [13,14].…”
Section: Introductionmentioning
confidence: 71%
“…[3] Moreover, the superconductivity transition occurs at 0.8 K under 26 kbar. [5] These two kinds of the coexistent states (2k F -SDW-2k F -CDW and 2k F -SDW-4k F -CDW) have been studied theoretically [6][7][8][9][10][11][12][13][14]. In these studies, they considered the inter-site Coulomb interaction (V ) in addition to the onsite Coulomb interaction (U ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we numerically investigate the 1D quarter-filled EHM coupled to the magnetic field via the Zeeman term. Although such a model was previously studied from several viewpoints, [10][11][12][13] how CO is affected by the magnetic field has been less discussed. By a quantum Monte Carlo method, we show that the CO correlation is enhanced by the applied magnetic field, and the behavior is continuously connected to the fully spin-polarized limit where exact results are known.…”
mentioning
confidence: 99%